Dusung Dati and Dusung Pusaka in a Livelihood Sustainability (Case Study in Ullath Village Maluku) - Jeanee Belthia Nikijuluw (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Utilization of management of dusung (agricultural land) communally by a household (clan) is part of the tradition of the people of Ullath Village, Maluku province, passed on for generations. This research highlights the phenomenon of norms and cultures that impact internal conflicts from the perspective of household and livelihood transition. This study aims to explore and analyse the causes of the household livelihood transition and identify the household’s strategies for livelihood sustainability. Observation, documentation, and in-depth interviews were conducted with clove farmers, tuan negeri (landlords), and kewang to collect relevant data. The results show that the dynamics of communal management of dusung in one household led to conflict. To resolve the conflict, the resolution was to plant cloves together with different gadihu plants as a symbol or identity of each owner. However, it did not resolve the whole conflict due to fraud, and in the end, the farmers chose to do other work. For their households’ livelihood sustainability, they did tipar mayang jobs by keeping and renting the dusung, and implementing the maano system. This study emphasizes the norms and culture of local communities related to the management of dusung, which can lead to conflicts and livelihood transitions